La competencia intercultural y la competencia pragmática en la enseñanza de español como lengua extranjera (ELE) - Spychała-Wawrzyniak, Małgorzata; Suñén Bernal, María del Carmen (Studia Romanica Posnaniensia, 2021)
The main purpose of this article is to present the development and evolution of two fundamental components of the communicative competence in the teaching of foreign languages: pragmatics and interculturality. We will analyze different visions of pragmatic competence and intercultural competence, which are sometimes treated as synonymous concepts. We will focus our attention on the problems observed in class as a consequence of the great diversity of cultural contexts in which Spanish is learned, highlighting the importance of activating the development of both competences in class and the need to learn to negotiate linguistic and cultural meanings within a cultural context different from that of the target language. Finally, we will present the results of a study carried out with students from a Polish and a German university, whose objective was to analyze the previous attitudes of students from different faculties towards two competences that should always go hand in hand: pragmatics and interculturality.